Hypotrichotic nevus of the scalp with multiple lesions. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2014)
Case report. A 6-month-old child was first observed due to the presence since birth of areas with thinner and less pigmented hair in the right parietal region. The baby was first born of parents in apparent good health. He was born in the fortieth week by natural delivery after a normal pregnancy; at birth he weighed 3,050 g and was 49 cm long. The family history was negative for alterations of the scalp and his physical and mental development in the first months was normal. The physical examination put in evidence in the right parietal region lighter, roundish, isolated, 2-3 cm in diameter areas (Fig. 1). In the frontal region there was a clockwise whorl. The dermoscopic observation (Fig. 2) of the lighter areas showed a normal density of the hair, which, however, appeared thinner and lighter. These data led to the final diagnosis of hypotrichotic nevus of the scalp.